A non-coding CRHR2 SNP rs255105, a cis-eQTL for a downstream lincRNA AC005154.6, is associated with heroin addiction. - Orna Levran; Joel Correa da Rosa; Matthew Randesi; John Rotrosen; Miriam Adelson; Mary Jeanne Kreek (PLoS ONE)
Dysregulation of the stress response is implicated in drug addiction; therefore, polymorphisms in stress-related genes may be involved in this disease. An analysis was performed to identify associations between variants in 11 stress-related genes, selected a priori, and heroin addiction. Two discovery samples of American subjects of European descent (EA, n = 601) and of African Americans (AA, n = 400) were analyzed separately. Ancestry was verified by principal component analysis. Final sets of 414 (EA) and 562 (AA) variants were analyzed after filtering of 846 high-quality variants. The main result was an association of a non-coding SNP rs255105 in the CRH (CRF) receptor 2 gene (CRHR2), in the discovery EA sample (Pnominal = .00006; OR = 2.1; 95% CI 1.4-3.1). The association signal remained significant after permutation-based multiple testing correction. The result was corroborated by an independent EA case sample (n = 364). Bioinformatics analysis revealed that SNP rs255105 is associated with the expression of a downstream long intergenic non-coding RNA (lincRNA) gene AC005154.6. AC005154.6 is highly expressed in the pituitary but its functions are unknown. LincRNAs have been previously associated with adaptive behavior, PTSD, and alcohol addiction. Further studies are warranted to corroborate the association results and to assess the potential relevance of this lincRNA to addiction and other stress-related disorders.